Application of Icosahedral Phase Compound for Mesoporous Layer Material in Dye-Sensitized Solar Cells. (2017) - Alami, Abdul Hai; Assad, Mhd Adel; Aokal, Kamilia; Rajab, Bilal; Alawadhi, Hussain
Abstract: This paper presents the results obtained for dye-sensitized solar cells with an Al65 Cu24 Fe11 mesoporous layer replacing the conventional TiO2 layer. The synthesis of the icosahedral quasicrystalline Al-Cu-Fe compound is done by high energy ball milling to ensure the highest possible diffusion of the starting powder elemental materials, and the evolution of the desired microstructure is monitored via X-ray diffraction, scanning electron microscopy and energy dispersive x-ray spectroscopy. The optical absorption and electrical properties of the compound was characterized by spectrometry, four probe measurement, as well as Mott-Schottky analysis, respectively, and compared with those of TiO2 . Natural beetroot dye sensitizer was used in this, where its optical absorptivity property has been investigated. A natural organic dye extracted from beetroot is selected for the application as it has the widest absorption at the UV-Vis range. Two identical cells are constructed, one with the reference TiO2 material and the other with Al-Cu-Fe icosahedral compound as the mesoporous layer. The electrical characteristic curves, efficiency and fill factor were calculated for both. Power conversion efficiency enhancement from 0.4% to 0.827% was shown.